2010
DOI: 10.1016/j.bbmt.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cytomegalovirus (CMV) Reactivation after Umbilical Cord Blood Transplantation

Abstract: This study investigated the impact of pre-transplant CMV serostatus and post-transplant CMV reactivation and disease on umbilical cord blood transplant (UCBT) outcomes. Between 1994 and 2007, 332 patients with hematologic malignancies underwent UCBT and 54% were CMV seropositive. Pre-transplant recipient CMV serostatus had no impact on acute or chronic GVHD, relapse, DFS or OS. There was a trend toward greater day 100 TRM in CMV seropositive recipients (p=0.07). CMV reactivation occurred in 51% (92/180) of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 50 publications
9
73
0
3
Order By: Relevance
“…It is also possible that the lower risk of relapse reported in UCB transplantation 33 is associated with CMV reactivation. 34 CMV infection may induce expression of a ligand that activates either CD8 ϩ T cells and/or NK cells. Our data support the possibility that CMV infection may induce NK cells with increased potential to eliminate residual leukemic blasts.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the lower risk of relapse reported in UCB transplantation 33 is associated with CMV reactivation. 34 CMV infection may induce expression of a ligand that activates either CD8 ϩ T cells and/or NK cells. Our data support the possibility that CMV infection may induce NK cells with increased potential to eliminate residual leukemic blasts.…”
Section: Discussionmentioning
confidence: 99%
“…12,[56][57][58][59][60] Cytomegalovirus (CMV) is the most frequent opportunistic pathogen thought to contribute significantly to HSCT morbidity and mortality. 61 The CMV source after UCBT is almost exclusively of host origin because the incidence of congenital CMV infection is very low.…”
Section: Clinically Prognostic Value Of Thymopoietic Recovery After Ucbtmentioning
confidence: 99%
“…Development of anti-CMV responses in the absence of detectable viral replication was confirmed by staining with MHCpeptide tetramers. Reports showed that CMV infection can occur in CMV-seronegative patients receiving CMV-seronegative grafts, with an incidence ranging from 1.2 to 12% in the first 3 mo posttransplantation (10,13,22,62). However, to our knowledge, kinetics of antiviral immune reconstitution were never assessed in CMV-seronegative patients receiving CMV-seronegative grafts.…”
Section: Discussionmentioning
confidence: 90%
“…Major advantages of UCBT include a low incidence of graft-versus-host disease (GvHD) (4) and an efficient graft-versusleukemia effect (5) graftment, late reconstitution of the CD8 + T cell subset, and a higher incidence of opportunistic infections in the first 3-6 mo posttransplantation that results in higher morbidity and mortality relative to BMT during this period (6)(7)(8). In particular, CMV and varicella zoster virus (VZV) are important causes of opportunistic infections, and infections with these pathogens are observed more frequently in UCBT recipients than in BMT recipients (9,10).…”
mentioning
confidence: 99%